The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12974-017-1044-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-VC701-PET and MRI in the in vivo neuroinflammation assessment of a mouse model of multiple sclerosis

Abstract: BackgroundPositron emission tomography (PET) using translocator protein (TSPO) ligands has been used to detect neuroinflammatory processes in neurological disorders, including multiple sclerosis (MS). The aim of this study was to evaluate neuroinflammation in a mouse MS model (EAE) using TSPO-PET with 18F-VC701, in combination with magnetic resonance imaging (MRI).MethodsMOG35-55/CFA and pertussis toxin protocol was used to induce EAE in C57BL/6 mice. Disease progression was monitored daily, whereas MRI evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
(57 reference statements)
2
23
0
Order By: Relevance
“…Similar to our previous study, results in this paper clearly determined morphological changes in the neurons and elevation in glia cellularity in Met treated animals. We observed histo-morphological changes such as swelling of neuronal cell bodies linked with the dysregulation of metabolic ratio (decrease in tNAA/tCr and increase in tCho/tCr) and changes in the volumetric analysis which is consonant to the previous studies from different laboratories [40,41] and clinical studies [18,42]. This indicates that different types of the development of hHcy conditions (direct Hcy subcutaneous administration or by Met-enriched diet) could lead to the different levels of histological damage, probably influenced by Hcy itself or its toxic metabolites.…”
Section: Histo-morphological Changes In the Brain After Met Diet-indusupporting
confidence: 89%
“…Similar to our previous study, results in this paper clearly determined morphological changes in the neurons and elevation in glia cellularity in Met treated animals. We observed histo-morphological changes such as swelling of neuronal cell bodies linked with the dysregulation of metabolic ratio (decrease in tNAA/tCr and increase in tCho/tCr) and changes in the volumetric analysis which is consonant to the previous studies from different laboratories [40,41] and clinical studies [18,42]. This indicates that different types of the development of hHcy conditions (direct Hcy subcutaneous administration or by Met-enriched diet) could lead to the different levels of histological damage, probably influenced by Hcy itself or its toxic metabolites.…”
Section: Histo-morphological Changes In the Brain After Met Diet-indusupporting
confidence: 89%
“…Authors also found an abundance of CD11b+ GAMs inside and around the tumour [248]. We have recently developed and characterised a new TSPO radiotracer, [ 18 F]VC701 in neuroinflammation models [249]. Similarly, in an orthotopic glioma model obtained with murine GBM cells, the GL261 ones, we observed an earlier TSPO uptake signal compared to [ 18 F]FLT uptake (Figure 2).…”
Section: Cancer and Inflammationmentioning
confidence: 65%
“…TSPO ligands have been inuredin experimental autoimmune encephalomyelitis (EAE), a well-accepted animal model for MS is effective in highlighting neuropathological features of MS, inclusive ofmicroglial activation [18]. 18F-VC701-PET helps to detect and follow microglia activation evolution .when18F-VC701-PET copulate with prevalent T1-gadolinium-enhanced and T2 MRI imaging theEAE-related impairments can be identified [19].…”
Section: Discussionmentioning
confidence: 99%